2020
DOI: 10.3892/etm.2020.8900
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of treatment for primary tracheal tumors by flexible bronchoscopy: Airway stenosis recanalization and quality of life

Abstract: The aim of the present study was to evaluate the effectiveness of interventional treatment of primary tracheal tumors through flexible bronchoscopy. The clinical data of 38 patients with primary tracheal tumours who underwent flexible bronchoscopy intervention therapy between January 2011 and January 2017 were retrospectively analyzed. The average time interval from onset of symptoms to the appearance of actual clinical manifestations in the 38 patients ranged from 0 to 60 months, with an average of 8.1±11.6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The criterion standard management of tracheal schwannoma is open surgical tracheal resection with end-to-end anastomosis. APPROVED GALLEY PROOF However, it is not suitable for long segmental tracheal resection [17]. Reports of the use of endoscopic excision of this tumor have increased in recent literature [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The criterion standard management of tracheal schwannoma is open surgical tracheal resection with end-to-end anastomosis. APPROVED GALLEY PROOF However, it is not suitable for long segmental tracheal resection [17]. Reports of the use of endoscopic excision of this tumor have increased in recent literature [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not suitable for long segmental tracheal resection [ 17 ]. Reports of the use of endoscopic excision of this tumor have increased in recent literature [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not suitable for long segmental tracheal resection, owing to the lack of an ideal material for a tracheal substitute. 1 Alternative treatment consists of a complete endoscopic approach, especially in patients whose tumors were pedunculated-type and intraluminal. 10 Of note, there were some cases of tumor local recurrence after endoscopic resection, 5 , 8 , 11 whereas no relapse was recorded in surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…Primary tracheal tumor is an uncommon disease, with an estimated incidence of one case per million. 1 The majority of these neoplasms are malignancies and mostly consists of squamous cell carcinoma and adenoid cystic carcinoma. 2 Primary tracheal neurogenic tumors are extremely rare, constituting less than 0.5% of primary tracheal tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Five-year survival rates of malignant tracheal tumors in non-surgically and surgically treated patients are 10% and 50%, respectively. A retrospective study focused on multiple primary tracheal tumors showed that 90% of cases were recanalized with the use of multiple bronchoscopy procedures leading to significant dyspnea improvement [ 8 ].…”
Section: Discussionmentioning
confidence: 99%